Model biomasy igliwia sosny zwyczajnej (Pinus sylvestris L.) wyrosłej w warunkach gruntów porolnych i leśnych - Jelonek, Tomasz; Pazdrowski, Witold; Tomczak, Arkadiusz; Walkowiak, Ryszard (Leśne Prace Badawcze, 2012)
The relationship between the biometric traits of Scots pine ( Pinus sylvestris L .) trees and their total needle biomass was analysed and the foliage of these trees growing in 38 stands in northern and western Poland was modelled. Productive pine stands were chosen on former farmland and forest soil providing locally optimal conditions for growth. A total of 114 trees aged between 32 and 114 years old were felled and their total biomass of fresh needles was calculated. Out of all the traits measured, diameter at breast height (DBH) was the best predictor of foliage biomass. Since the two models produced to describe this relationship on forest soils (Mi = 0.093614 D 1.3 1.679398 ), and farmland (Mi = 0.060302 D 1.3 1.819009 ) were very similar, they may be used interchangeably. However, as they aged, needles of pines growing on former farmland deteriorated faster than those on forest soil with respect to their assimilation capacity. This suggests that the assumptions of Pipe Model Theory need to be verified.